Explicating the dynamics of project capabilities. Issue 2 (February 2016) - Davies, Andrew; Brady, Tim
Abstract: This article provides a foundation to guide future research on project capabilities based on three main contributions. First, drawing upon research on dynamic capabilities and organisational ambidexterity, we suggest that innovative and routine dimensions of project capabilities are developed and mobilised to deal with the variety of exploratory and exploitative conditions facing an organisation. Second, we distinguish between project capabilities at the operational and dynamic capabilities at the strategic levels, arguing that firms depend on identifiable dynamic capabilities (e.g. portfolio management techniques) to know when and how to maintain current project capabilities and when to modify or replace them depending on the conditions encountered. Third, we suggest that the relationship between dynamic and project capabilities is reciprocal, recursive and mutually reinforcing. In this reciprocal relationship, the emergence of new or declining project capabilities provides indications for the strategic priorities, behaviours and future deployment of an organisation's dynamic capabilities.